Hubungan Peran Orang Tua Dengan Cakupan Imunisasi Dasar Lengkap Selama Pandemic di Lhokseumawe - Haifa Ayu Dinarsono Putri; Mauliza Mauliza; Khairunnisa Khairunnisa; Mardiati Mardiati; Noviana Zara (Lembaga Pengembangan Kinerja Dosen, 2025)
The coverage of complete basic immunization in Indonesia in 2020 during the Covid-19 pandemic had not yet reached the expected target. The province with the lowest coverage was Aceh, with only 41.8%, indicating a significant gap from the national target. This study aims to determine the relationship between parental roles and the coverage of complete basic immunization for infants during the Covid-19 pandemic in the Banda Sakti area. This research used a cross-sectional design with a cluster sampling technique. The univariate analysis showed that most of the children were male, totaling 48 (51.6%). The age of the fathers was mostly between 26–35 years (52 respondents or 55.9%), and the mothers’ age was also mostly between 26–35 years (63 respondents or 67.7%). The majority of both fathers and mothers had a senior high school education, with 49 (52.7%) and 39 (41.9%) respectively. Most of the basic immunization coverage in the Banda Sakti area was incomplete, amounting to 74 infants (79.6%), and the parental role was categorized as poor. The bivariate analysis using the Chi-square test and its alternatives showed a p value < 0.05, indicating a significant relationship between the roles of fathers, mothers, and parents in general, and the coverage of complete basic immunization. The conclusion of this study is that there is a significant relationship between parental roles and the coverage of complete basic immunization for infants during the Covid-19 pandemic in the Banda Sakti area.